1991
DOI: 10.1007/bf02316874
|View full text |Cite
|
Sign up to set email alerts
|

A rapid method for evaluating the behavioral effects of phencyclidine-like dissociative anesthetics in mice

Abstract: A simple and rapid method for detecting the behavioral effects of phencyclidine and related dissociative anesthetics is described. Dissociative anesthetics such as phencyclidine (PCP) and dizolcipine, which bind with high affinities at N-methyl-D-aspartate (NMDA) coupled cation channels ("PCP receptors"), produced a dose-related increase in the percentage of mice that fell from a 1.5 cm deep circular arena mounted on a 60 cm platform. A similar behavior was not manifest by other classes of compounds examined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…We confirmed that the antidepressant-like action of 4-Cl-KYN in the acute FST involves the glycine B site, since pretreatment with glycine prevented the effects at the same dose shown to increase concentrations of glycine in the brain (albeit by less than a 2-fold difference) and to reverse the behavioral effects of NMDA channel blockers (Trullas and Skolnick, 1990;Evoniuk et al, 1991;Javitt et al, 1999). In support, no off-site receptor targets were identified by the extensive receptor screening performed (Supplemental Figs.…”
Section: Fast-onset Antidepressant Effects Of 4-chlorokynureninesupporting
confidence: 72%
See 2 more Smart Citations
“…We confirmed that the antidepressant-like action of 4-Cl-KYN in the acute FST involves the glycine B site, since pretreatment with glycine prevented the effects at the same dose shown to increase concentrations of glycine in the brain (albeit by less than a 2-fold difference) and to reverse the behavioral effects of NMDA channel blockers (Trullas and Skolnick, 1990;Evoniuk et al, 1991;Javitt et al, 1999). In support, no off-site receptor targets were identified by the extensive receptor screening performed (Supplemental Figs.…”
Section: Fast-onset Antidepressant Effects Of 4-chlorokynureninesupporting
confidence: 72%
“…; Evoniuk et al (1991); Javitt et al (1999)]. Whereas glycine administration alone did not change immobility time of saline-treated animals in the FST, it prevented the antidepressant-like effects of 4-Cl-KYN (25 mg/kg) in this paradigm (Fig.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Compounds that trigger psychedelic-like effects and a dissociative-like state, which partly resembles the anesthetic state, are termed dissociative anesthetics (Evoniuk et al, 1991;Yamakura et al, 2000;Zorumski et al, 2016). Dissociation refers to the disruption of usually integrated functions, such as consciousness, memory, emotions, and behavior (Carlson et al, 2018).…”
Section: E Dissociative Anestheticsmentioning
confidence: 99%